ADMINISTRATIVE REQUIREMENTS FOR ACTIVE PARTICIPATION IN NATIONAL HEALTH INSURANCE REGISTRATION OF TRANSFER OF LAND RIGHTS FOR SALE AND PURCHASE - Maharani, Nikita Dwi (Zhata Institut, 2024)
This legal research investigates the nexus between the administrative requirement of active participation in the National Health Insurance (NHI) and the registration of the transfer of land rights in the context of property transactions. Employing a juridical-normative approach, the study meticulously analyzes legal regulations, legal doctrines, and court decisions relevant to land transfer registrations and the prerequisites of active NHI participation. The examination reveals that compliance with NHI administrative requirements has the potential to impact the smoothness of land transfer registration processes, and violations of these conditions may result in significant legal consequences. Therefore, a deeper understanding of this relationship provides practical guidance for stakeholders involved in land transactions and contributes to the development of pertinent policies that balance administrative and legal considerations within the framework of NHI and land rights registration.